Origin and Evolution of RNA-Dependent RNA Polymerase - de Farias, Savio T.; dos Santos Junior, Ariosvaldo P.; Rêgo, Thais G.; José, Marco V. (Frontiers in Genetics, 2017)
RNA-dependent RNA polymerases (RdRp) are very ancient enzymes and are essential for all viruses with RNA genomes. We reconstruct the origin and evolution of this polymerase since the initial stages of the origin of life. The origin of the RdRp was traced back from tRNA ancestors. At the origin of the RdRp the most ancient part of the protein is the cofactor binding site that had the capacity of binding to simple molecules as magnesium, calcium and ribonucleotides. Our results suggest that RdRp originated from junctions of proto-tRNAs that worked as the first genes at the emergence of the primitive translation system, where the RNA was the informational molecule. The initial domain, worked as a building block for the emergence of the fingers and thumb domains. From the ancestral RdRp, we could establish the evolutionary stages of viral evolution from a rooted ancestor to modern viruses. It was observed that the selective pressure under the RdRp was the organization and functioning of the genome, where RNA double stranded and RNA single stranded virus formed a separate group. We propose an evolutionary route to the polymerases and the results suggest an ancient scenario for the origin of RNA viruses.